Has the Controversy on the Jurisdiction of Federal High Court over Unregistered Trade Marks Matters Finally Been Resolved? - Umaru, M. J.; Anigbogu, Bridget; Doma, Halima (ABUAD Law Journal, 2023)
The uncanny characteristics of unregistered trade marks (TM) and its enforceability in Nigerian courts leave a wild imagination as to its legal protection and the appropriate court to seek redress and enforcement. Not only is the status of unregistered TM shaky, there is also the question as to which court can enforce same. Thus, the coordinate adjudicatory powers of the Federal High Court and the State High Court have been put to test in this instance. A joint reading of the Nigerian Constitution and the Trade Marks Act seem to have robed the Federal High Court of its exclusive or unilateral original jurisdiction to hear and determine TM cases in general. Yet, these statutory provisions enjoin divergent judicial pronouncements for and against the courts in issue. This paper reviewed the statutory provisions on trademarks and passing off as well as the Supreme Court decisions on the issue with a view to determining whether the apex court has overruled itself in its earlier decisions, now generally conferring exclusive jurisdiction on Federal High Court, in respect of all matters relating to trademarks and passing off particularly for non registered TM.The paper concluded that the latest pronouncement of the Supreme Court on the issue was predicated on the subsisting and applicable law then as well as the peculiar facts of the case and, therefore, not a clear departure from its earlier position on unregistered trademarks.